Iniciativa cintur\~ao e rota na América Latina: Entre ades\~oes e hesitaç\~oes - Carlos Renato Ungaretti; Ticiana Gabrielle Amaral Nunes; Giulia Marianna Rodrigues Di Marco; Marco Aurélio Alves de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The present article analyzes the recent expansion of the Belt and Road Initiative (BRI) in Latin America and the Caribbean (LAC). The study is justified by the noticeable increase and diversification of economic relations between the region and China in recent years. The advance of the BRI in Latin America is interpreted in line with the theoretical and conceptual contributions of the field of International Cooperation for Development (ICD). Specific cases of Latin American countries have been analyzed and their particularities highlighted. It is argued that these countries' decision to join the initiative is not a homogeneous phenomenon, but endowed with multiple potentials and challenges.
10419/284874
Keywords: F10; F30; F34; F50; F55; F59; F6; 330; China; Latin America and the Caribbean; Belt and Road Initiative; foreign direct investment; infrastructure